(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the importance of using modern tools and software to optimize the transport system in the field of road engineering to ensure its efficient and safe operation. This topic covers the study of new technologies, understanding their principles of operation, and applying them to more efficient and effective road construction and management processes.